Safety evaluation of the food enzyme phytepsin from Cynara cardunculus L. - EFSA Panel on Food Contact Materials, Enzymes and Processing Aids (CEP); Claude Lambré; José Manuel Barat Baviera; Claudia Bolognesi; Pier Sandro Cocconcelli; Riccardo Crebelli; David Michael Gott; Konrad Grob; Evgenia Lampi; Marcel Mengelers; Alicja Mortensen; Gilles Rivière; et al. (EFSA Journal)
Abstract The food enzyme phytepsin (EC 3.4.23.40) is extracted from the pistils of the cardoon (Cynara cardunculus L.) by different manufacturers represented by the Dirección General de Salud Pública, Gobierno de Canarias, España. It is intended to be used in milk processing for cheese production. As no concerns arose from the source of the food enzyme, from its manufacture, and based on a history of safe use and consumption, the Panel considered that toxicological data and the estimation of dietary exposure were not required. A search for the similarity of the amino acid sequences of the food enzyme to known allergens was made and no matches were found. The Panel considered that allergic reactions to this phytepsin cannot be excluded in individuals allergic to cardoon. However, the likelihood of allergic reactions to the phytepsin from C. cardunculus L. is expected not to exceed the likelihood of allergic reactions to cardoon. As the prevalence of allergic reactions to cardoon is low, also the likelihood of such reactions to occur to the food enzyme is low. Based on the data provided, the Panel concluded that this food enzyme does not give rise to safety concerns under the intended conditions of use.